Repolymerisation of lignins extracted from wood pulps through enzymatic modification to establish viable valorisation routes - Du Toit, Chante Mirri (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.